Standardization and Development of Process for Sheerqurma and its Shelf-Life Study - A, Syed K (Indian Journal of Dairy Science, 2018)
The aim of this investigation was undertaken to utilize drynuts in milk to make a Sheerqurma by standardize a percent of khoa by treatment T0 (0%), T1(5%), T2 (10%)and T3 (15%)then the percent of sugar by treatment T4 (10%), T5(15%)and T6 (20%). The Sheerqurma was prepared by standardized processing parameter and subjected to sensory analysis using 9 point Hedonic scale and physicochemical parameter. Based on sensory analysis and physicochemical parameter, treatment T5 containing 5% khoa and 15% sugar obtained the highest sensory score. It was revealed from the results that there is gradual increase in acidity, specific gravity, density, T.S.S, total solid as percent of khoa or sugar increased where pH and moisture was decreased. The product was evaluated for its shelf life stability in LDPE, HDPE pouch, PET and Glass bottle in refrigerator at 4ÂºC by sensory analysis and microbial count on interval of alternate day till 9 days. According to sensory analysis and microbial count Sheerqurma can remained stable till 5th day in glass bottle. While in LDPE, HDPE pouch Total Plate Count and Coliform was observed on 3rd day and in PET bottle observed on 5th day. Similarly yeast and mould observed on 5th day after the incubation of 3 days.